2011
DOI: 10.1007/s11738-011-0736-6
|View full text |Cite
|
Sign up to set email alerts
|

Anther culture in pepper (Capsicum annuum L.) in vitro

Abstract: Pepper (Capsicum annuum L.) is an important vegetable crop that can be improved using plant tissue culture and biotechnology. However, it is difficult to develop appropriate breeding material by in vitro cultivation in this species. Haploid plant production is useful in the breeding programs to facilitate recovery of recessive mutations and unique genetic recombinations. In embryogenesis, haploid formation from pollen in anther culture is a scientifically advanced, but controversial system. Various techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 65 publications
2
64
0
2
Order By: Relevance
“…Anther cultures have been used in a number of cultivars with relative efficiency (reviewed in Irikova et al 2011;Seguí-Simarro et al 2011), but successful application of microspore cultures has only been reported in few hot (asian) pepper types (Kim et al 2008;Supena et al 2006b). Nevertheless, the stages most sensitive to inductive treatments in pepper revolve around the VM and YBP (Irikova et al 2011), exactly the same described for most of the known inducible species. Pepper is not an exception in this sense.…”
Section: Introductionmentioning
confidence: 99%
“…Anther cultures have been used in a number of cultivars with relative efficiency (reviewed in Irikova et al 2011;Seguí-Simarro et al 2011), but successful application of microspore cultures has only been reported in few hot (asian) pepper types (Kim et al 2008;Supena et al 2006b). Nevertheless, the stages most sensitive to inductive treatments in pepper revolve around the VM and YBP (Irikova et al 2011), exactly the same described for most of the known inducible species. Pepper is not an exception in this sense.…”
Section: Introductionmentioning
confidence: 99%
“…The several reasons for this inefficiency in production of callus or embryo-like structures from anthers and subsequent plant regeneration include the genotypic dependence, collection of donor buds in the optimal stage, stress treatments as well as composition of medium and the culture conditions (Kothari et al, 2010 andIrikova et al, 2011).…”
Section: Issn: 2319-7706 Volume 6 Number 5 (2017) Pp 925-933mentioning
confidence: 99%
“…Despite the considerable number of studies conducted with pepper anther culture, the reported effectiveness of the process is still low (Irikova et al, 2011a). A high frequency of anther-derived embryos can be obtained, but few of them develop into normal plants (Segui-Simarro et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%